اثر برنامج تدريبي للقوة الانفجارية للرجلين علي تطور اداء قفزة اليدين علي منصة القفز لطلاب قسم التربية الرياضية جامعة النيلين - محمود, عوض يس احمد; الحسيناوي, ناظم حمد عكاب (Sulaimani Journal for Humanities, 2018)
The objective of the research was to design a training program to develop the performance of the jump of the hands on the jumping table using the explosive force training of the muscles of the two men in the students of the Department of Physical Education University of Neelain and the two experimental methods used the system of control groups and experimental, the sample was randomly selected from the students of the Department of Physical Education, (10 students per group), and the appropriate tools were used and the application of the prepared curriculum, and the collection and processing of data statistically using the statistical bag, the two researchers reached the most important results as there is a function in favor of the experimental group, Training. The researchers recommend to encourage trainers to use the method of exercises with explosive force, which has an impact on the development of the physical and skill in order to move away from traditional methods.